Satisfaction with police services among victims of physical assault in India: Impact of quality of procedure and outcome of process - Kumar, TK Vinod (International journal of police science & management, 2017)
Victim satisfaction is impacted by both the quality of the procedure and the outcome of the criminal justice process. Quality of procedure encompasses procedural and interactional justice. Using survey data of victims of physical assault in India, this study examines the impact of quality of procedure and outcome on victim satisfaction with police services. The study concludes that although both factors have an effect on victim satisfaction, quality of procedure has a greater impact than outcomes of the process for victims of physical assault in India.